Basic electronics a text-lab manual - Zbar, Paul B. 1911- (Basic electricity-electronics series, 1994)
For this edition, experiments have been written in a down-to-earth style so that students can grasp the most fundamental concepts. State-of-the-art materials are used in the exercises, and use of modern equipment is encouraged. The experimental procedures have been written in a manner requiring the student to think and make decisions.